2012
DOI: 10.2522/ptj.20110252
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock-Wave Therapy for Supraspinatus Calcifying Tendinitis: A Randomized Clinical Trial Comparing Two Different Energy Levels

Abstract: BackgroundExtracorporeal shock-wave therapy (ESWT) represents a valid intervention in the treatment of people with supraspinatus calcifying tendinitis (SCT), but there is limited evidence for the useful range of ESWT doses.ObjectiveThe aim of this study was to compare 2 different ranges of energy flux density in treatment of SCT with ESWT.Design Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 52 publications
1
62
1
1
Order By: Relevance
“…An open or an arthroscopic approach may be used. An energy level of 0.20 mJ/mm [ 2 ] appears to be more effective than an energy level of 0.10 mJ/mm [ 2 ] in pain relief and functional improvement [ 9 ] I A single high-level ESWT may be as effective as two applications of a lower-dosed ESWT [ 10 ] II Calcifying tendonitis of the shoulder -evidence according to treatment Treatment Evidence Level of evidence Acetic acid iontophoresis and physiotherapy Treatment with both modalities did not result in better clinical or radiologic effects than those observed in subjects treated with physiotherapy alone [ 11 ] I Acromion morphology…”
Section: Treatment Strategymentioning
confidence: 86%
“…An open or an arthroscopic approach may be used. An energy level of 0.20 mJ/mm [ 2 ] appears to be more effective than an energy level of 0.10 mJ/mm [ 2 ] in pain relief and functional improvement [ 9 ] I A single high-level ESWT may be as effective as two applications of a lower-dosed ESWT [ 10 ] II Calcifying tendonitis of the shoulder -evidence according to treatment Treatment Evidence Level of evidence Acetic acid iontophoresis and physiotherapy Treatment with both modalities did not result in better clinical or radiologic effects than those observed in subjects treated with physiotherapy alone [ 11 ] I Acromion morphology…”
Section: Treatment Strategymentioning
confidence: 86%
“…Nine studies (8 RCTs), including a total of 346 patients, used high-energy ESWT as the treatment modality. 23,24,[29][30][31][32][33][34]36 Although these trials all used highenergy ESWT, the reported EFD (0.2 to 0.55 mJ/mm 2 ), number of pulses applied (1,000 to 2,400), and number of sessions (1 to 4) varied. The shockwave energy was focused on the calcific deposit in 6 trials and on the maximum point of tenderness in 2 trials.…”
Section: High-energy Eswtmentioning
confidence: 92%
“…The ConstantMurley Scale (CMS) 42 was the most commonly reported shoulder function outcome measure. In addition to the CMS, 5 studies used the American Shoulder and Elbow Surgeons (ASES) 43 29 and Ioppolo et al 31 described the change in size in square millimeters.…”
Section: Outcome Measures: Type and Timingmentioning
confidence: 99%
“…Both groups were found to have improved outcomes at each time point; however, the VAS scores were statistically reduced and the CMS were higher at 6 months in the higher energy group (0.20 mJ/mm 2 ). The authors also noted that clinical improvement did not correlate with a reduction in size of calcifications [73].…”
Section: Upper Extremity Pathologymentioning
confidence: 94%
“…Ioppolo et al [73] studied patients with calcific tendinitis of the supraspinatus tendon. Forty‐six patients were randomized to either receive 4 weekly sessions of ESWT using 2400 pulses at 0.20 or 0.10 mJ/mm 2 , and a control group was not present.…”
Section: Upper Extremity Pathologymentioning
confidence: 99%